EFFICACY OF ONDANSETRON ALONE VERSUS ONDANSETRON WITH DEXAMETHASONE IN PREVENTING POSTOPERATIVE NAUSEA OR VOMITING IN PATIENTS UNDERGOING ENT SURGERY - Umer Rafique; Palwasha Khan Kasi; Shakil Malik; Vijai Kumar; Hiranand; Rajesh Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Postoperative nausea and vomiting (PONV) are common after Ear, Nose, and Throat (ENT) surgeries due to various factors. Addressing PONV effectively is crucial for patient recovery and satisfaction.Objective: This study compared the efficacy of ondansetron alone versus ondansetron with dexamethasone in preventing PONV in ENT surgery patients.Methodology: A six-month prospective study enrolled 138 ENT surgery patients, randomly assigning them to receive ondansetron alone (Group A) or ondansetron with dexamethasone (Group B). Efficacy was assessed by nausea and vomiting occurrence within six hours post-surgery.Results: Group B showed significantly higher efficacy in preventing PONV compared to Group A (Group A: 62.3% vs. Group B: 84%, p=0.004). While nausea occurrence was lower in Group B, vomiting occurrence did not significantly differ between groups. Group B had fewer multiple vomiting episodes, indicating better efficacy.Conclusion: Combining ondansetron with dexamethasone provides superior PONV prophylaxis in ENT surgery patients compared to ondansetron alone. This highlights the potential for optimizing perioperative care and patient outcomes in ENT surgeries. Further research is needed to validate these findings.